Los movimientos de población en el área septentrional del Conventus Carthaginensis - Hurtado Aguña, Julián (Gerión. Revista de Historia Antigua, 2005)
This article analyses the population displacements,that lived in the Meridional Plateau during the Roman epoch, towards to other parts of the Peninsula. Especially important was the Tarraco influence’s, wich attracted people from the South Plateau, they had militar or religious charges in these town. In other way inmigrants, wich lived in the cities of the northern part of the Conventus Carthaginensis, basically came from cities of northern Plateau and east coast